Geocehmical analysis of inorganic bulk sediment from two sites in the East China Sea drilled during IODP Exp346 - Chloe H Anderson; Richard W Murray; Ann G Dunlea; Liviu Giosan; C W Kinsley; David McGee; Ryuji Tada (PANGAEA, 2019)
We examine the paleoceanographic record over the last 400 kyr derived from major, trace, and rare earth elements in bulk sediment from two sites in the East China Sea drilled during Integrated Ocean Drilling Program Expedition 346. We use multivariate statistical partitioning techniques (Q-mode factor analysis, multiple linear regression) to identify and quantify five crustal source components (Upper Continental Crust (UCC), Luochuan Loess, Xiashu Loess, Southern Japanese Islands, Kyushu Volcanics), and model their mass accumulation rates (MARs). UCC (35–79% of terrigenous contribution) and Luochuan Loess (16–55% contribution) are the most abundant end-members through time, while Xiashu Loess, Southern Japanese Islands, and Kyushu Volcanics (1–22% contribution) are the lowest in abundance when present. Cycles in UCC and Luochuan Loess MARs may indicate continental and loess-like material transported by major rivers into the Okinawa Trough. Increases in sea level and grain size proxy (e.g., SiO2/Al2O3) are coincident with increased flux of Southern Japanese Islands, indicating localized sediment supply from Japan. Increases in total terrigenous MAR precede minimum relative sea levels by several thousand years and may indicate remobilization of continental shelf material. Changes in the relative contribution of these end-members are decoupled from total MAR, indicating compositional changes in the sediment are distinct from accumulation rate changes but may be linked to variations in sea level, riverine and eolian fluxes, and shelf-bypass processes over glacial-interglacials, complicating accurate monsoon reconstructions from fluvial dominated sediment.
Supplement to: Anderson, CH et al. (2018): Climatically Driven Changes in the Supply of Terrigenous Sediment to the East China Sea. Geochemistry, Geophysics, Geosystems, 19(8), 2463-2477, https://doi.org/10.1029/2017GC007339